2009
DOI: 10.4103/0972-6748.62263
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obsessive compulsive symptoms among patients with schizophrenia

Abstract: Background:Obsessive compulsive symptoms in schizophrenia are well recognized but are a less-researched entity. These symptoms have important implications for management and prognosis.Aim:To find out the prevalence of obsessive compulsive symptoms among patients with schizophrenia.Materials and Methods:A total of 90 hospitalized patients with schizophrenia diagnosed according to DCR of ICD-10 criteria were selected for the study. Padua inventory and Yale-Brown Obsessive Compulsive Scale were applied to find ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This finding may be consistent with studies in the literature reporting a high proportion of obsessive compulsive symptoms in depressed patients [11]. About schizophrenia, instead, the presence of obsessive symptoms appears to be more relevant in this study than in the literature (54% v s. 10-26%) [17,18]. It may be due to differences in measuring sexual obsessions between studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding may be consistent with studies in the literature reporting a high proportion of obsessive compulsive symptoms in depressed patients [11]. About schizophrenia, instead, the presence of obsessive symptoms appears to be more relevant in this study than in the literature (54% v s. 10-26%) [17,18]. It may be due to differences in measuring sexual obsessions between studies.…”
Section: Discussionsupporting
confidence: 89%
“…In schizophrenia, obsessive compulsive symptoms were reported by 10% [17] to 26.7% of patients, the frequent obsessions being that of contamination, sexual and aggressive thoughts [18]. Although OCD co-occurs in a substantial proportion of schizophrenia patients [19], the rate of occurrence and the clinical effect of sexual obsessions have been scarcely investigated in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts the findings of Devi and Wehbe, who found no influence on the QOL. 5,37 One reason for the initial results implying a poor QOL in this study could be the severe symptoms seen in schizophrenia patients with OCS. Another reason could be that OCS often compound other symptoms or are signs of a specific pathophysiologic pathway intimately associated with maladaptive or lack of adaptive behavior.…”
Section: Discussionmentioning
confidence: 87%
“…However, it should be noted that the recent report by Devi et al did not reveal any differences in the severity of schizophrenia symptoms between schizophrenia patients with and without OCS, warranting the need for large-scale, prospective research on this topic. 5,25,37 Some studies have also suggested that discrepancies in diagnosing obsessions in the presence of delusions could contribute to a positive association between OCS and positive symptoms, pointing towards the need for a consensus definition for diagnosis and research in this area. 34 In this study, OCS were associated with higher degrees of impairment in general functioning and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…The most common obsessions were contamination and sexual images and the compulsions being cleaning and praying which are similar to those reported earlier. [30]…”
Section: Discussionmentioning
confidence: 99%